Penggunaan Model Pembelajaran Problem Based Learning berbantuan Media Visual dalam Meningkatkan Kemampuan Pemecahan Masalah Matematis Siswa SMP - Kurniawan, Dian (LPPM Universitas Bina Bangsa, 2025)
This study aims to investigate the effect of using the Problem-Based Learning (PBL) model assisted by visual media on junior high school students’ mathematical problem-solving skills. The background of this research lies in the fact that many students still struggle to connect abstract mathematical concepts with their practical applications in everyday life. PBL was chosen because it positions students as active learners involved in analyzing and solving real-world problems, while visual media serves as a tool to concretize abstract concepts, making them easier to understand. The research method employed was quantitative with a quasi-experimental design, using a pretest-posttest control group design. The sample consisted of two classes of eighth-grade students (32 students each), selected through purposive sampling. The experimental class received instruction using the PBL model assisted by visual media, while the control class was taught using conventional methods. The research instrument was a mathematical problem-solving test in the form of essay questions based on Polya’s four problem-solving stages. Data were analyzed using normality, homogeneity, and independent t-tests. The findings revealed a significant difference between the experimental and control groups. The experimental group achieved a higher posttest mean score (81.6) compared to the control group (70.3), with average N-Gain scores of 0.65 (medium-high category) and 0.42 (medium category), respectively. The independent t-test produced a significance value of 0.000 < 0.05, indicating a positive and significant effect of implementing PBL with visual media on students’ mathematical problem-solving abilities. Therefore, it can be concluded that the combination of PBL and visual media is effective in enhancing mathematical understanding, critical thinking skills, and making mathematics learning more contextual and meaningful for junior high school students.